1994
DOI: 10.1007/bf00232634
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation and plant regeneration of watermelon using Agrobacterium tumefaciens

Abstract: Adventitious shoots formed on the proximal cut edges of different cotyledonary explants of watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai; cvs. Sweet Gem and Gold Medal] cultured on Murashige and Skoog's (MS) medium with 1 mgl(-1) 6-benzyladenine (BA). Light (16-h photoperiod, about 7 Wm(-2) cool-white fluorescent lamps) was essential for shoot formation. To obtain transformed plants, cotyledonary explants of 'Sweet Gem' were cocultured with Agrobacterium tumefaciens LBA4404, a disarmed strain harborin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 8 publications
6
55
1
3
Order By: Relevance
“…Seedling age is reported to be an important factor for obtaining high frequency adventitious shoot regeneration in watermelon (Choi et al, 1994;Compton & Gray, 1994). For watermelon organogenesis, explants were collected from seedlings younger than five-dayold (Choi et al, 1994;Compton, 2000), as young cotyledons are physiologically very active and respond efficiently to exogenous hormones (Dong & Jia, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seedling age is reported to be an important factor for obtaining high frequency adventitious shoot regeneration in watermelon (Choi et al, 1994;Compton & Gray, 1994). For watermelon organogenesis, explants were collected from seedlings younger than five-dayold (Choi et al, 1994;Compton, 2000), as young cotyledons are physiologically very active and respond efficiently to exogenous hormones (Dong & Jia, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Together with seedling age, explant type has shown to be important for morphogenesis induction, since competent cells for adventitious shoot formation in cucurbits seem to be restricted to specific cotyledon regions (Choi et al, 1994;Compton, 2000;Ananthakrishman et al, 2003). For watermelon, it has been shown that organogenic competent cells concentrated at the proximal region of the cotyledon (Compton & Gray, 1993), since most of the adventitious buds develop at the explant basal region (Compton, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…품종의 종자증식 시간의 단축 때문에 많은 관심을 받고 있다 (Choi et al, 1994;Compton and Gray, 1994;Tabei, 1997). 그 러나 이러한 형질전환체 개발이나 유용한 품종 육성은 기내 재 분화 기술의 실질적인 적용방법과 효율성 때문에 제한된 품종 에 국한되고 있다 (Wang et al, 2013).…”
Section: 수박 유묘 자엽을 이용한 신초 재분화 기술에 관한 연구는 신 초 기관형성 체세포배 형성 원형질체 배양 unclassified